Purse-string suture with nylon cords and metal clips for the treatment of duodenal fistulae under the endoscope: a case report - Wang, Lei; Zhang, Ruiya; Wang, Bochu; Zhou, Guoxiong; Zhou, Xiaorong; Meng, Run (Frontiers in Medicine, 2024)
Purse-string suture with nylon cords and metal clips under the endoscope is a novel minimally invasive treatment technology, and it is particularly indicated for the closure and repair of gastrointestinal fistula or perforations such as duodenal fistulae. Duodenal fistulae are often caused by medical manipulation, disease progression or trauma. Once this occurs, it leads to a series of pathophysiologic changes and a variety of complications. In most cases, these complications will exacerbate the damage to the organism, are difficult to treat and can lead to infections, nutrient loss, multi-organ dysfunction and many other adverse effects. In this case report, the use of endoscopic nylon cords combined with metal clip purse string suture in the treatment of duodenal fistula is presented and discussed. The patient was treated with endoscopic purse-string suture and the duodenal fistula was significantly improved. The results indicate that endoscopic purse-string suture is an effective strategy for the treatment of duodenal fistulae.